Apple turnover murder - Fluke, Joanne, 1943- (Fluke, Joanne, 1943- Hannah Swensen mystery., 2010)
Hannah has excellent reasons to despise the caddish Bradford Ramsey, as do many other women. Nevertheless, she'd rather not expose her youthful indiscretions, especially to her policeman beau. Hannah is very busy with the mayor's wife Lake Eden, Minn. charity event at which Ramsey is host. So what should she say when she stumbles upon his murdered corpse?